Cost Effective System Using for Bioimpedance Measurement - Nguyen, Phan Kien; Tran, Anh Vu (Old Journal, 2019)
This paper presents an economical system for measuring the bioimpedance of meat. The measurement is based on the electrical Fricke model and the inverting configuration of operational amplifiers (op-amp). The system can generate testing signals with frequency ranged from 10Hz to 1MHz and adjustable amplitude up to 1.08Vpp. The sweeping input and output of the op-amp are captured by an oscilloscope that is connected to and controlled by a computer before being processed by MATLAB. The system allows performing automatic customizable sweep routines. Generally, the measurement on a resistor and a RC meat-modeling circuit and a meat sample provided favorable results. In the future, system will be used for measurement and assessment meat quality in order to create a new methods for assessment of food quality.